"Now that you've got that coverage": Promoting use of a regular source of primary care among homeless persons. Issue 2 (13th February 2021) - Dickins, Kirsten; Buchholz, Susan W.; Ingram, Diana; Hamilton, Rebekah J.; Braun, Lynne T.; Karnik, Niranjan S.; Earle, Melinda
ABSTRACT: Background: The growing number of homeless persons in the United States demonstrates greater morbidity and mortality than the population as a whole. Homeless persons are often without a regular source of primary care. Homeless persons use emergency departments and are hospitalized at higher rates than nonhomeless persons. In 2010, the enactment of the Affordable Care Act expanded access to primary care services. Nurse practitioners were at the forefront of its subsequent implementation. Purpose: The purpose of this qualitative study was to explore the factors that influence establishing and maintaining a regular source of primary care among homeless persons. Methodological orientation: In 2017, semistructured interviews were conducted in a federally qualified health center that serves predominately homeless persons. Sample: A purposive convenience sample included adult health center users ( N = 20). The majority of participants were insured (90%), African American (70%), and male (65%). Conclusions: Thematic analysis revealed five facilitators: sense of community, mutual patient–provider respect, financial assurance, integrated health services, and patient care teams. To establish and maintain use of a regular primary care source, homeless persons desire to experience a sense of community, feel respected by their provider/staff, and have certainty that costs will not exceed their capacity to pay. Integrated care models that leverage a multidisciplinary team approach support the use of a regular primary care source. Implications for practice: Actualizing achievable strategies that promote the consistent use of a regular primary care source can reduce use of avoidable emergency and hospital-based services, thereby improving health outcomes among homeless persons.